Eco-Tourism Practices for Sustainable Development in Himachal Pradesh - Kumar, Sandeep; Gupta, Neeru; Pathania, Kulwant Singh (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Himachal Pradesh is a state blessed with stunning natural beauty, featuring majestic mountains, perennial rivers, picturesque valleys, and a rich cultural heritage. Tourism serves as the second leading source of income, after agriculture. Visitors flock to the hill stations to escape the heat of the plains and rejuvenate before returning to their routines. Mountains provide a variety of adventure activities including trekking, hiking, and camping, allowing individuals to connect with nature. Many seek inner peace and happiness in these serene landscapes. However, it is crucial to prioritize the conservation of the environment, preservation of local culture, and enhancement of the region’s economy. This paper reviews existing studies and emphasizes the eco-tourism practices in Himachal Pradesh.